An Analysis of Human Resource Training and Development at Pizza Hut Restaurant, Riau Branch, Bandung City - Priadi, Muhammad Dadi; Berliana, Regina; Guterres, Alexandre De Sousa (Commercium : Journal of Business and Management, 2024)
This research was conducted to find out how training and development was provided to employees at Pizza Hut Restaurant, Riau Branch, Bandung City. The purpose of this research is to find out and analyze the training and development provided by trainers and managers at Pizza Hut, as well as the influence of training and development on employee performance at Pizza Hut Restaurant, Riau Branch, Bandung City. This research uses qualitative research methods with descriptive analysis research type. The sources obtained used data collection techniques using observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing/verification. The data validity techniques used include credibility, transferability, dependability and confirmability tests. The subject of qualitative research is the main instrument of the researcher. Meanwhile, the object of this research is Pizza Hut Restaurant, Riau Branch, Bandung City. The results of this research are (1) the training provided at Pizza Hut, Riau Branch, Bandung City is quite good, the training stages are in accordance with existing theories (2) Trainers always carry out training by reviewing it every month to test the extent of their abilities. employees (3) Performance assessment and evaluation for employees at Pizza Hut Restaurant Riau Branch, Bandung City is not going well (4) The development program carried out by managers at Pizza Hut Riau Branch is quite good, work performance increases with competition to get employee rewards , become motivated and enthusiastic at work (5) The employee accident rate has decreased where employees work in accordance with the work safety program. However, there are still tools and machines that need attention so that they can work more efficiently (6) Employee discipline shows a decreasing level, which can be caused by a lack of supervision and strict rules. Apart from that, the workforce used must be comprehensive (7) The development methods at Pizza Hut have been running in accordance with theory, but from the point of view the educational methods are still not in accordance with the theory applied. Training and development of employees at Pizza Hut must continue to be considered to improve employee performance and achieve company targets